2020
DOI: 10.1007/s00238-020-01735-8
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid: a simple way to reduce drainage and bleeding in rhytidoplasty

Abstract: Background Hematoma is the most common complication in facelift surgery. It has a reported incidence ranging from 0.2 to 8%. Tranexamic acid (TXA) is an antifibrinolytic agent capable of minimizing blood loss, and its use in plastic surgery is quite new. The literature review indicates that there are no formal guidelines for dosing and standardization of TXA use. We sought to evaluate the efficacy of intraoperative local irrigation of TXA in reducing the incidence of hematomas in patients undergoing facelift s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The populations of previous studies were smaller, and we used a different facelift technique. 27,31,47 To date, there are multiple ways to administer TXA including oral, topical, intravenous, and infiltration/tumescent administration, but there is no standard way in facial rejuvenation procedures. 28,48 Although other studies used TXA as irrigation, or by a local, tumescent, or intravenous route, 27,31,47 we used both local infiltration and the intravenous route with strict regulation of the doses to maximize optimal results without increasing the risk of side effects or related complications.…”
Section: Discussionmentioning
confidence: 99%
“…The populations of previous studies were smaller, and we used a different facelift technique. 27,31,47 To date, there are multiple ways to administer TXA including oral, topical, intravenous, and infiltration/tumescent administration, but there is no standard way in facial rejuvenation procedures. 28,48 Although other studies used TXA as irrigation, or by a local, tumescent, or intravenous route, 27,31,47 we used both local infiltration and the intravenous route with strict regulation of the doses to maximize optimal results without increasing the risk of side effects or related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with subjective appraisals of perioperative bleeding, drain output is readily quantifiable and may present a good indicator of the effectiveness of TXA. After the use of TXA-containing tumescent or irrigation, two studies reported drain output to be reduced by 70% on POD1 compared with the control, with 95% of drains having less than 25 mls output [6,30]. This led to a statistically significant increase in drains being removed on POD1.…”
Section: Clinical Effectsmentioning
confidence: 99%
“…Serrano Reyes et al examined 24-h drainage output, complications, and hematoma formation post-rhytidectomy [2]. Overall, 20% of patients developed a hematoma; however, the drainage was 71% lower in the TXA group compared to the control group; 10 (range 8-22) ml vs. 35 (range 19-50) ml, respectively (p = 0.009) [2]. Fayman et al examined the effects of mixing TXA with diluted local anesthetic solution to make a tumescent solution that maximizes surgical success while simultaneously minimizing side effects.…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
“…Overall, beneficial outcomes of statistical significance in studies involving IV use of TXA in liposuction, mastectomy, rhinoplasty, septoplasty, and rhytidectomy procedures included decline in intraoperative bleeding [48,55], rate of postoperative hematoma [2,60], periorbital ecchymosis, decreased eyelid edema [48,52,55,63], shorter duration of surgery, improved surgical filed [51], increase of surgeon satisfaction, and a more rapid return to social activity (Table 3) [52].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
See 1 more Smart Citation